The Nursing Students’ Needs of English for Specific Purposes to Minimize Difficulty in Learning English - Syaiful Haque; Dwi Rukmini; Januarius Mujyanto (English Education Journal, 2022)
The English nursing curriculum used in university is considered to have problems regarding its relevance and appropriateness to meet students’ professional and academic needs. This study addressed this issue by investigating the English language skills needed in academic and occupational contexts. The objective of this study were: (1) to explain English language skills that students have difficulties with in English Program, (2) to explain the Nursing students’ needs in an academic and professional context, and (3) to explain the relationship between students’ needs and the achievement. This study employed a case study research design by using using Dudley-Evans and St. John’s (1998) needs analysis as the research framework. The researchers used a quantitative research design that was triangulated with qualitative to obtain different and complementary data. The participants of this study were 58 students in Nursing Study Program at a university, 2 English lecturers, and 5 former students that have worked in hospitals as employees. The results showed that: (1) most of the students have serious difficulties almost in all English language skills that they need for their academic study and also their future carrier; (2) students need better English language skills; (3) there are discrepancies in the perception of students need between students and English teacher (4) the information of students ‘needs will influence the achievement of students in teaching and learning English because it will help teacher as an important and powerful factor in the ESP classroom to adapt the most appropriate courses for the students.